Graphene screen‐printed radio‐frequency identification devices on flexible substrates. Issue 11 (4th October 2016) - Arapov, Kirill; Jaakkola, Kaarle; Ermolov, Vladimir; Bex, Guy; Rubingh, Eric; Haque, Samiul; Sandberg, Henrik; Abbel, Robert; de With, Gijsbertus; Friedrich, Heiner
Abstract : Despite the great promise of printed flexible electronics from 2D crystals, and especially graphene, few scalable applications have been reported so far that can be termed roll‐to‐roll compatible. Here we combine screen printed graphene with photonic annealing to realize radio‐frequency identification devices with a reading range of up to 4 meters. Most notably our approach leads to fatigue resistant devices showing less than 1% deterioration of electrical properties after 1000 bending cycles. The bending fatigue resistance demonstrated on a variety of technologically relevant plastic and paper substrates renders the material highly suitable for various printable wearable devices, where repeatable dynamic bending stress is expected during usage. All applied printing and post‐processing methods are compatible with roll‐to‐roll manufacturing and temperature sensitive flexible substrates providing a platform for the scalable manufacturing of mechanically stable and environmentally friendly graphene printed electronics. Abstract : Fabrication and performance investigation of screen‐printed graphene radio frequency identification (RFID) devices realized on flexible substrates is demonstrated. Sheet resistance of 5 Ω/□ and lower is achieved using optimized photonic annealing and subsequent compression rolling. A reading distance of the graphene devices up to 4 meters is reported and it does not deteriorate even after 1000 bending cycles demonstrating excellent mechanical stability.